Development of a lacustrine terminal fan and a coarse grained delta in the tertiary Daban Basin (Norfhern Somalia) - Abbate, E.; Bruni, P.; Sagri, M. (Cuadernos de Geología Ibérica, 1991)
The Daban Basin developed in a rapidly subsiding half graben of the Gulf of Aden rift system. It is filled with 2700 m of transitional to continental clastie deposits of Middle Eocene to Oligocene age. Toward the top of the succession, perennial lake sediments interfinger with a thick delta sequence. The basal portion of this delta system consists of conglomeratie mouth-bars deposited in shallow water at the lacustrine margin. The middle and upper portions include stacked and horizontally laminated sandstone units, deposited at the lake margin as a terminal fan whieh was fed by ephemeral streams during a period of aridity. The moutb bar delta was a very efficient depositional system which eonveyed sands to the centre of the lake. In contrast, the terminal fan was dominated by sheet flows and built up mainly in the marginal area of ihe lake, but run-off from rare large storms transported sandy material to tbe centre of the perennial lake. Sediment supply and facies distribution in the delta complex were controlled by climatic changes and by the asymmetric geometry of Ihe basin that guided the stream drainage.